KARAKTERISASI TEPUNG EMPAT VARIETAS PISANG DI LEMBAH PALU - Kadir, Syahraeni (FAPETKAN UNTAD, 2005)
A laboratory work was carried out to characteristize the flour of banana of 4 different cultivars (i.e. Tsnduk, Kepok, Cavendish, Emas) cultivated in palu valley region. It was found that the banana of cv Tanduk and Kepok were more suitable for flour production since the had higher content of flour (18,91% – 21.4%) than those of cv Cavendish and Emas. The fuit of Cavendish and Emas seemed to be more suitable to be processed as table fruit. Key words : Flour, banana, characteristize, cultivars.